The liver recipient with acute renal dysfunction: A single institution evaluation of the simultaneous liver‐kidney transplant candidate. Issue 1 (24th November 2017) - Yadav, Kunal; Serrano, Oscar K.; Peterson, Kent J.; Pruett, Timothy L.; Kandaswamy, Raja; Bangdiwala, Ananta; Ibrahim, Hassan; Israni, Ajay; Lake, John; Chinnakotla, Srinath
Abstract: The Organ Procurement Transplant Network (OPTN) listing criteria for simultaneous liver‐kidney transplant (SLK) are not well defined. Concerns remain about rising numbers of SLKs, which divert quality kidneys from candidates awaiting kidney transplants (KT). We performed a retrospective review of liver transplants (LTs) at our center from 2004 to 2014; 127 recipients (liver transplant alone; 102 LTA, 25 SLK) were identified with short‐term preoperative kidney dysfunction (creatinine >4 mg/dL or preoperative hemodialysis [HD] for <6 weeks). Both cohorts had comparable baseline demographic characteristics with the exception of higher model for end‐stage liver disease (MELD) score in the LTA group (41.4 vs 32.9, P  < .0001) and higher incidence of pre‐LT diabetes in the SLK cohort (52% vs 26.5%, P  = .0176). Duration of pre‐LT HD was higher in SLK recipients, but the difference was not statistically significant ( P  = .39). Renal nonrecovery (RNR) rate in LTA cohort was low (<5%). No significant difference was noted in 1‐year mortality, liver graft rejection/failure, or length of stay (LOS) between the cohorts. Thus, it appears that liver recipients with short‐term (<6 weeks) HD or AKI without HD have comparable outcomes between LTA and SLK. With provisions for a KT safety net, as proposed by OPTN, LTA may be the most adequate option for these patients.